Consequences of an emerging China : is development space disappearing for Latin America and the Caribbean? - Phillips, Nicole (The Centre for International Governance Innovation WaterlooCA, 2007)
Examines the nature of the emerging economic relationship between Latin America and the Caribbean and China. Seeks to offer some reflections on the significance of this relationship for Latin American and Caribbean development.